Pencapaian Keunggulan Kompetitif Perusahaan Dengan Pengelolaan Sumber Daya Manusianya - Setiawan, Teguh (Media Mahardhika, 2017)
Competitive advantage is created with the sole purpose of making the value that the company had no other place. The problem is, with a wide range of access and flow of information, often competitive value did not last long. Competitive advantage can be created through the management of human resources effectively by pursuing a strategy to create and achieve competitive advantage. There are 13 strategies in the management of human resources as a source of competitive advantage to achieve a competitive advantage of companies that can be implemented by the division includes Human Resources Department; 1) employement security, 2) selective in recruitin, 3) high wages, 4) incentive pay, 5) employee ownership, 6) information sharing, 7) participation and empowerment, 8) self-managed team, 9) Cross utilization and training, 10) symbolic egalitarian, 11) wage compretion, 12) reduces interpersonal competition and improve efficiency through collaboration, and 13) promotion from within. This strategy is intended to create human resources; 1) valuable, 2) rare, 3) difficult, to imitate, and 4) difficult, to substitute. Fourth it becomes an attribute of human resource characteristics that can increase a companys competitive advantage